2004
DOI: 10.1081/css-120038565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Nitrogen Rates on Open-Field Vegetable Growth and Nitrogen Utilization in the North China Plain

Abstract: Advanced nitrogen (N) advisory systems require target values of N supply for the crop and the results of soil testing for inorganic nitrogen (N min ) before cultivation and estimates of N release from mineralization. Two field experiments with different N supply levels were conducted in the Beijing region to determine the target values of N supply and N mineralization rates for optimization of N fertilization of Chinese cabbage (Brassica campestris L. ssp. Pekinensis) and carrot (Daucus carota L.). Crop yield,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The N treatment was with laboratory grade urea incorporated at 0, 200 and 500 kg N/ha. Urea N rates were selected based on the information that the agronomically effective N supply level for Chinese cabbage was about 350 kg N/ha for target marketable yields of 120 t/ha (Chen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The N treatment was with laboratory grade urea incorporated at 0, 200 and 500 kg N/ha. Urea N rates were selected based on the information that the agronomically effective N supply level for Chinese cabbage was about 350 kg N/ha for target marketable yields of 120 t/ha (Chen et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…6). Leafy plants are best for trapping nitrogen from the wastewater, but its growth can be impaired if sufficient nitrogen is not available (Chen et al, 2004). Rakocy (1999) reported that the tomato growth was good enough in aquaponics system.…”
Section: Sampling Datesmentioning
confidence: 99%
“…Reported net mineralization rates for fields in continuous crop production were 150 kg N ha -1 for a sandy soil in Germany (Gutezeit 1999), 46 kg N ha -1 for a loam soil over the winter growing season in China (Chen et al 2004), 77-146 kg N ha -1 yr -1 for course loam soil in New Brunswick (Zebarth et al 2004), <100->300 kg N ha -1 yr -1 for various mineral soils in Ontario (Kay et al 2004), and up to 1250 kg N ha -1 yr -1 for organic soil in Florida (Reddy 1982).…”
Section: Nitrogen and Carrot Yield Quality Andmentioning
confidence: 99%